Longitudinal differences in the injury profile of professional male handball players according to competitive-level - Raya-González, J.; García-Esteban, S.; de Ste Croix, M.; Clemente, F. M.; Castillo, D. (Research in Sports Medicine, 2021)
The aim was to analyse the differences in professional handball players` injury profile according to the team`s competitive-level (i.e., First division vs. Second division). Fifty-three professional male handball players participated in this study during four consecutive seasons in the same team (2015-16 and 2016-17 for the First division league and 2017-18 and 2018-19 for the Second division league). No significant differences in overall incidence were observed between groups (3.69 vs 4.19 injuries/1000h, RR=0.88, 95% CI 0.64-1.22, P =0.44), although significantly greater injury incidence during training sessions was observed in the Second division group (3.06 vs 1.61 injuries/1000h, RR=0.52, 95% CI 0.34-0.81, P =0.01), while greater injury incidence during matches was reported in the First division group (84.03 vs 49.88 injuries/1000h, RR=1.68, 95% CI 1.00-2.83, P =0.05). The second division group presented the greatest injury burden attending to overall, training and match exposure, as well as in most locations and injury types. Given the between groups differences found in the injury profile of handball player, it is suggested to implement specific preventive strategies attending to the characteristics of each level-group.